AN ANALYSIS OF STUDENTS’ LEVEL OF CRITICAL THINKING IN FINAL EXAM - Novia Gerungan; Meity Muntuuntu; Rinny Rorimpandey (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
This research aims to determine whether the final exam that is given by the teacher to students can encourage students to think critically. This research was conducted in Tondano. The method used in this research was the quantitative method. The researcher took the data from about English language exam consisting of 40 questions. In 40 questions there are 5 kinds of test that is examined. Research using the theory of Bloom's Taxonomy. After being analyzed based on the theory of bloom’s taxonomy, all the contents of the questions contain 100% knowledge. In 40 questions there is no comprehension, application, analysis, synthesis, or even evaluation. The test results showed that the 40 questions are at the level of low order thinking because it's a matter of the English exam is otherwise not able to encourage the students in critical thinking according to the theory of Bloom's Taxonomy on high order thinking level.